PENERIMAAN PUBLIK TERHADAP PELAYANAN PERUSAHAAN AIR MINUM DALAM PENGARUH KEPERCAYAAN SOSIAL DAN KUALITAS PELAYANAN: (Survei Pada Pengguna Layanan PDAM Tirta Sewakadarma, Kota Denpasar) - Elsafani Hariyanto (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
Water resources which are universal in every aspect of life have an important role in supporting activities in various fields. The need for water for every human being makes it classified as a public good. Perumda Tirta Sewakadarma Drinking Water seeks to provide drinking water to fulfill the needs of the community in order to have a healthy, clean and productive life. However, based on the community's assessment on Google Reviews, Perumda Tirta Sewakadarma has a rating of 1.5 out of 5. This shows that the people of Denpasar's trust in Perumda Tirta Sewakadarma is relatively low. This study aims to see the effect of society's trust on public acceptance of drinking water service policies in PDAM Tirta Sewakadarma. This study uses a quantitative method with SEM-PLS analysis. The results of this study indicate that the Social Trust variable has a significant effect on Public Acceptance. Therefore, the Service Quality variable has a significant effect in moderating the Social Trust variable on Public Acceptance